P111 Older patients with tuberculosis have less typical changes on chest radiographs. (15th November 2016) - Abbara, A; Mahomed, Z; Collin, SM; Kon, OM; Bushell, V; Buell, K; Sullivan, JAL; Hansel, T; Corrah, T; Davidson, RN
Abstract : Introduction and objectives: It has been suggested that TB has a different phenotype in older patients with age-related changes to the cell-mediated immune response and co-existent organ dysfunction. Older patients with tuberculosis (TB) may have different radiographic features than younger patients; this may lead to less immediate suspicion of TB resulting in delays to diagnosis and starting treatment. We wanted to identify if there are differences in the most common radiological differences in older and younger patients with pulmonary TB (PTB). Methods: Patients with PTB > 65 were noted from the London TB register between 2002 and 2015. A random selection of younger patients aged 18–40 with PTB were also identified. All available chest x-ray (CXR) reports were obtained from online radiology systems. CXR features were classified according to reported features with particular note of cavitation, nodules and miliary changes, consolidation, lymphadenopathy and effusions. Results: The CXR reports of 239 patients with PTB < 65 and 99 patients with PTB > 65 were collated. Demographic details as well as CXR changes are detailed in Table 1 . Cavitation, lymphadenopathy and effusions were more common in younger patients whereas consolidation was more evident in older patients. Upper zone involvement was similar in both groups. Conclusions: Studies by other groups have suggested a higher proportion of cavitation and upper zone changes in younger patients with TB with less specific changes in older patients. This may lead to less suspicion of TB and potentially a longer infective period; this is important given that 23% and 19% of younger and older patients have smear positive PTB. In our study, the proportion with upper zone changes are similar though cavitation is more frequent in younger patients. Of note, is the much higher presence of lymphadenopathy and effusions seen in younger patients. This may potentially be related to differences in the immune function of both groups or primary infection versus reactivation. These findings re-enforce the need for clinical suspicion for PTB in both older and younger patients with both specific and non-specific radiographic changes.